(untitled) (Journal of Science and Technology, 2016)
A descriptive-correlational survey research design was used to establish Game Ranger’s perceptions of their existing levels of motivation, job satisfaction, recognition, supervision, perceived competence and role clarity. The relationships among these variables as well as age and number of years’ experience as a game ranger were also examined. The results indicated perceived low levels of recognition, average levels of motivation, job satisfaction, perceived competence and supervision, and a high level of role clarity. Significant relationships were found between the following variables; Job satisfaction and Recognition (r 37); Supervision and Recognition (r 40); Motivation and Job Satisfaction (r 41), Motivation and Recognition (r 40);